Seismic Behavior of GFRP Tube Reactive Powder Concrete Composite Columns With Encased Steel - Ji, Jing; He, Lingjie; Jiang, Liangqin; Ren, Hongguo; Ni, Shuai; Wang, Zizhen; Li, Yunhao; Yu, Chenyu; Lin, Yubo (Frontiers in Materials, 2021)
To obtain the seismic behavior of glass fiber reinforced polymer (GFRP) tube reactive powder concrete composite columns with encased steel (GRS), a total of 17 full-scale GRS columns were designed in this paper. The parametric studies were conducted to explore the influence of factors such as the diameter of GFRP tube (D), thickness of GFRP tube (t), number of fiber winding layers (n), fiber winding angle (θ), axial compression ratio (λ), compressive strength of reactive powder concrete (fc), the area of encased steel (As) and strength of encased steel (fsy) on the seismic behavior of the composite columns. The finite element models of this kind of columns were established by ABAQUS finite element software, and the seismic behavior analysis for GRS composite columns was carried out. The results show that all the specimens exhibit good ductility and strong deformation ability. The stiffness degradation of specimens significantly slow down with increasing of D, fsy and λ. The energy dissipation capacity of specimens can be improved by increasing of D and λ, while the increasing of As and fsy leads to the decreasing of the energy dissipation capacity. By observing the failure mode of such composite columns, local bulging occurs in the foot area of the columns. Based on the statistical analysis of the calculated results, the restoring force models for GRS composite columns are proposed, which agree well with the simulated results. The restoring force models can provide reference for the elastic-plastic seismic response analysis of this kind of composite columns.